A shared cognitive user task framework for elearning storyboard / Nor'ain binti Mohd Yusoff - Nor'ain, Mohd Yusoff (2015)
This thesis presents a framework which is aimed to achieve shared mental model (SMM) needed between instructional designers and subject-matter experts called as the eSCOUT (eLearning Storyboard for Shared Cognitive User Task). The eSCOUT is built to facilitate shared input, shared process and shared output. The shared input refers to the data process that derived from the knowledge and needs of instructional designer and subject-matter expert. The shared process refers to storyboard design process methodology which is designed to support agility and consists of three cognitive user task processes: pre-processing, processing and post-processing. Several types of shared visualizations techniques are proposed to support shared cognitive user task in these processing phases. At the pre-processing stage, collaborative mapping is used to support shared structural design of the storyboard requirement while at the processing stage; collaborative whiteboard is used to support shared storyboard design specifications. At the post-processing stage, both collaborative discussion and collaborative annotation are used to support shared reviews of the storyboard design. Finally, the shared output is the shared cognitive user task information generated in a form of shared data visualization. To implement the framework of the eSCOUT, a web-based system prototype is developed. Experimental study on shared mental model is carried out among users of real instructional design practices. Using paired groups of instructional designers and subject-matter experts, the result shows that effectiveness of the agile storyboarding process is perceived as 64.3% compare to efficiency capabilities of the process which is 50%. All the tools available (i.e. collaborative mapping, collaborative whiteboard, collaborative discussion and collaborative annotation) are perceived as different from what the users have experienced in other storyboard system. The findings also showed that both collaborative map and collaborative whiteboard are flexible in terms of sharing v the data and performing eLearning tasks as well as easy to learn the functionalities. Our evaluation study demonstrates high achievement of similarity and accuracy of the shared data visualization, in turn leading to the development of task mental model. Consequently, it also shows effectiveness and efficiency of the agility support in the storyboarding design process as well as high usability scores of the shared visualizations techniques.